Eating Disorders in Athletes: The Female Athlete Triad and RED-S - A Literature Review - Fidyk, Monika; Bolek, Michał; Jagieła, Bartosz; Kędzia, Aleksandra; Musialska, Dominika; Minkiewicz, Magda; Dyda, Maciej (Quality in Sport, 2025)
Athletes, particularly females involved in aesthetic or endurance sports, are at increased risk for developing eating disorders (EDs), which are frequently linked to low energy availability (LEA). LEA, whether intentional or unintentional, disrupts physiological systems and underlies both the Female Athlete Triad and the broader concept of Relative Energy Deficiency in Sport (RED-S). This review examines the prevalence, diagnostic approaches, health consequences, and treatment strategies for EDs in athletic populations. The physiological consequences of LEA include hormonal imbalances, menstrual dysfunction, impaired bone mineral density (BMD), cardiovascular abnormalities, and reduced metabolic and immune function. Psychological factors such as perfectionism, body dissatisfaction, and stress susceptibility are both contributors to and consequences of LEA-related disorders. These issues significantly compromise athletic performance by impairing recovery, increasing injury risk, and limiting training adaptations. Prevention strategies emphasize early education, targeted screening, and programs like ATHENA, which promote healthy behaviors and body image among adolescent athletes. Treatment focuses on restoring adequate energy availability through nutritional and behavioral adjustments, with pharmacological intervention considered only in select cases. Multidisciplinary support is essential for effective management and long-term recovery.